Methodological Tools for Evaluating Effectiveness of Capital Construction Projects of Oil Producing Enterprises - E. L. Chazov; V. P. Grakhov; O. L. Simchenko (Наука и техника)
Due to the fact that most of the large oil fields in Russia, characterized by high production costs, are at the final stage of development; the issue of cost optimization has become increasingly important in recent years. The main cost items at oil and gas enterprises are design and construction (reconstruction) of oil field facilities. Analysis of currently used methods for ranking oil and gas projects has shown that all of them are inherently subjective, since they are based on expert opinion. The authors have developed a methodological tools for evaluating the effectiveness of capital construction projects of oil field facilities (for example, construction work on the site for inventory receiving bridges and lifting units), which allows  to eliminate the influence of expert opinion  as much as possible and, consequently,  significantly  improve  the quality and validity of management decisions. The choice of the optimal project is based on a two – level assessment (stage 1– technical assessment, stage 2 – economic assessment). At each stage, an integral indicator is determined by calculation based on the results of objective data analysis  and using the developed algorithms. Thus, it is possible to judge the effectiveness of any project without being based on a subjective approach in the assessment with the help of expert opinion.